ROUTINE METHOD FOR THE DETERMINATION OF TRACE AMOUNTS OF 226Ra IN URINE BY ALPHA SPECTROMETRY. Issue 2 (19th July 2019) - Guérin, Nicolas; McMullin, Danielle; Fabian, Xenia; Kramer-Tremblay, Sheila; Gagné, Alexandre; Gale, Ashley
Abstract: 226 Ra is considered one of the most radiotoxic naturally occurring radionuclides. A new routine method was developed to measure traces of 226 Ra in urine. Radium was pre-concentrated from a 2 l urine sample using manganese oxide (MnO2 ) particles. The MnO2 precipitate was dissolved and the organic matter was broken down. Then, potential radiological interferents were removed using DGA and AGMP1 stacked resin columns. A barium sulphate (BaSO4 ) micro-precipitation was performed before measuring the sample by alpha spectrometry. A good recovery of 60 ± 10% and excellent alpha resolution were obtained. The minimum detectable activity (MDA) was 0.2 ± 0.1 mBql −1 . The method was validated using spiked samples and can be completed in 5 hours.